AkzoNobel doubles Chinese organic peroxides capacity; receives approval for separation. Issue 1 (January 2018) - Unknown
Abstract : In China, AkzoNobel's Specialty Chemicals business is implementing the next phase of a major expansion at its Ningbo organic peroxides plant, which will result in a doubling of production capacity there by the third quarter of 2018. The facility produces crosslinking agent dicumyl peroxide (DCP). In other news, the company's shareholders have formally approved plans for the separation of its Specialty Chemicals business.